Relaxing Effect of TSU-68, an Antiangiogenic Agent, on Mouse Airway Smooth Muscle - Honghao Tan (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Recently, some small-molecule compounds that were designed for cancer therapy have acquired new roles in the treatment of pulmonary diseases. However, drug screening aimed at abnormal muscle contraction is still limited. TSU-68 is a potent, orally administered, small-molecule agent that can reduce the vascular endothelial growth factor (VEGF)-induced Ca2+ increase in endothelial cells. We questioned whether TSU-68 could also affect calcium influx and relax airway smooth muscle (ASM) cells. The current study aimed to investigate these effects and to explore the underlying mechanisms. Methods: The effects of TSU-68 on ASM cells were studied in mice using a series of biophysiological techniques, including force measurement and patch-clamp experiments. Results: TSU-68 inhibited high K+ or acetylcholine chloride (ACh)-induced pre-contracted mouse tracheal rings in a concentration-dependent manner. Further research demonstrated that the TSU-68-induced ASM relaxation was mediated by calcium, which was decreased by blocking voltage-dependent Ca2+ channels (VDCCs) and non-selective cation channels (NSCCs). Conclusion: Our data indicated that TSU-68 relaxes tense ASM by reducing the intracellular Ca2+ concentration through blocking VDCCs and NSCCs, which suggested that this small molecule might be useful in the treatment of abnormal smooth muscle.